The Impact in Intestines and Microbiota in BALB/c Mice Through Consumption of Milk Fermented by Potentially Probiotic Lacticaseibacillus casei SJRP38 and Limosilactobacillus fermentum SJRP43 - de Souza, Bruna Maria Salotti; Guerra, Luiz Henrique Alves [UNESP]; Varallo, Giovanna Rossi; Taboga, Sebastião Roberto [UNESP]; Penna, Ana Lúcia Barretto [UNESP] (Springer Nature, 2025)
The present study aimed to evaluate the effect of consumption of milk fermented by Lacticaseibacillus (Lc.) casei SJRP38 and Limosilactobacillus (Lm.) fermentum SJRP43 on bacterial translocation, stool analysis, and intestinal morphology of healthy BALB/c mice. Potentially probiotic lactic acid bacteria, Lc. casei SJRP38, and Lm. fermentum SJRP43 were evaluated and analyzed for translocation, fecal analysis, and intestinal morphology of four groups of mice: water control (WC), milk control (MC), milk fermented by Lc. casei SJRP38 (FMLC), and milk fermented by Lm. fermentum SJRP43 (FMLF), in co-culture with Streptococcus thermophilus ST080. The results of the animal assay indicate that the population of Lactobacilli and Bidobacterium sp. in the gastrointestinal tract of BALB/c mice was greater than 6.0 log10 CFU/g, and there was no evidence of bacteremia due to the low incidence of bacterial translocation. Ingesting fermented milk containing Lc. casei SJRP38 and Lm. fermentum SJRP43 was found to promote a healthier microbiota, as it led to a reduction in Clostridium sp. and an increase in Lactobacilli and Bifidobacterium sp. in feces. Furthermore, the dairy treatments (MC, FMLC, and FMLF) resulted in taller intestinal villi and an increase in the frequency of goblet cells in the intestines. Overall, the consumption of fermented milk containing Lc. casei SJRP38 and Lm. fermentum SJRP43 strains was deemed safe and demonstrated beneficial effects on the intestines of BALB/c mice.
Keywords: Functional food; Gastrointestinal tract; Histology; Intestinal morphometry; Lactic acid bacteria